Feasibility of Recycling Excess Agricultural Nitrate with Electrodialysis. Issue 6 (1st November 2017) - Baker, John M.; Griffis, Timothy J.
Abstract : One of the most serious environmental problems associated with agriculture is excessive nitrate N in waters leaving fields. It is a health hazard in drinking water and a primary cause of hypoxia in ocean waters receiving drainage from agricultural regions. Recent mitigation efforts have focused on techniques that promote denitrification—conversion of excess agricultural nitrate to N2 . This seems inherently wasteful since industrial production of nitrate fertilizer from N2 requires a substantial input of energy and is a major source of greenhouse gas emissions. Thus, it is desirable to develop methods to recycle nitrate, keeping it in a form suitable for reuse as fertilizer. One possibility is electrodialysis, in which direct current is passed through alternating cation‐ and anion‐permeable membranes, creating separate streams of dilute and concentrated water. We tested the concept under controlled conditions in a greenhouse and in a field setting on a contaminated trout stream with nitrate N concentrations consistently above 20 mg L −1 . The solar‐powered field system removed 42% of the nitrate from water passing through it and concentrated it in a tank for subsequent application as fertilizer. The upper limit of concentration was approximately 520 mg L −1, above which precipitation of calcite limited operation. Economic analysis indicates that in comparison to denitrification methods such as bioreactors, electrodialysis is likely to be more expensive per unit of nitrate removed. The approach will be most feasible for situations in which nitrate concentrations are well above environmental standards for extended periods, to maximize operating time and nitrate removal rate. Core Ideas: Nitrate can be extracted from contaminated water and concentrated by electrodialysis. The concentrated nitrate can be reused as fertilizer. The degree to which nitrate can be concentrated is limited by mineral precipitation. The method is promising, but research is needed to reduce costs.